2014
DOI: 10.1111/1755-0998.12269
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for metagenomic DNA extraction and Illumina amplicon library preparation for faecal and swab samples

Abstract: Next-generation sequencing (NGS) technology has extraordinarily enhanced the scope of research in the life sciences. To broaden the application of NGS to systems that were previously difficult to study, we present protocols for processing faecal and swab samples into amplicon libraries amenable to Illumina sequencing. We developed and tested a novel metagenomic DNA extraction approach using solid phase reversible immobilization (SPRI) beads on Western Bluebird (Sialia mexicana) samples stored in RNAlater. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 62 publications
1
89
0
1
Order By: Relevance
“…The number of reads mapped to a sample ranged from 240 to 9,533,688, with 147/152 samples mapped to more than 10,000 reads. The wide distribution of reads to a multiplexed sample is not uncommon and is seen in other studies using Illumina platforms (24,25). Samples where more than 50% of the reads could not be assigned a bacterial phylum were deemed to be artifacts of sequencing and subsequently excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The number of reads mapped to a sample ranged from 240 to 9,533,688, with 147/152 samples mapped to more than 10,000 reads. The wide distribution of reads to a multiplexed sample is not uncommon and is seen in other studies using Illumina platforms (24,25). Samples where more than 50% of the reads could not be assigned a bacterial phylum were deemed to be artifacts of sequencing and subsequently excluded from analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The Mu-DNA method can be easily converted to SPRI purification by replacing the silica binding step with an SPRI protocol. However Vo and Jedlicka (2014) found SPRI to only have improved performance with less contaminated samples, such as avian oral and cloacal swab extractions. SPRI DNA purification is therefore best reserved for relatively clean environmental sample types, in particular clear lake and stream waters or tissue samples (see Mayjonade et al 2016).…”
Section: Adaptability Of Mu-dnamentioning
confidence: 99%
“…However we found that neither DNeasy Blood and Tissue nor the adapted Mu-DNA: Tissue/Water protocol could achieve inhibition-free DNA from turbid, algal rich waters (Water B) as effectively as DNeasy PowerWater or Mu-DNA: Water (data not shown). Solid phase reversible immobilisation (SPRI) DNA purification, based on Rohland and Reich (2012), can achieve higher DNA yield and purity than spin column based protocols (Vo and Jedlicka 2014). The Mu-DNA method can be easily converted to SPRI purification by replacing the silica binding step with an SPRI protocol.…”
Section: Adaptability Of Mu-dnamentioning
confidence: 99%
See 1 more Smart Citation
“…While publications analyzing bat diets have dominated the field (Symondson and Harwood 2014), significant advances in establishing effective protocols for processing minimally invasive avian samples now show it is possible to recover high quantities and qualities of DNA from avian fecal samples for downstream analysis (Vo and Jedlicka 2014). Trevelline et al (2016) successfully applied molecular techniques to reveal that Louisiana Waterthrush (Parkesia motacilla) nestlings consumed larger percentages of lepidopterans and dipterans than was expected.…”
Section: Introductionmentioning
confidence: 99%